Cirrhotic cardiomyopathy: the liver affects the heart - Carvalho,M.V.H. (2019)
Cirrhotic cardiomyopathy historically has been confused as alcoholic cardiomyopathy. The key points for diagnosis of cirrhotic cardiomyopathy have been well explained, however this entity was neglected for a long time. Nowadays the diagnosis of this entity has become important because it is a factor that contributes significantly to morbidity-mortality in cirrhotic patients. Characteristics of cirrhotic cardiomyopathy are a hyperdynamic circulatory state, altered diastolic relaxation, impaired contractility, and electrophysiological abnormalities, particularity QT interval prolongation. The pathogenesis includes impaired function of beta-receptors, altered transmembrane currents and overproduction of cardiodepressant factors, such as nitric oxide, cytokines and endogenous cannabinoids. In addition to physical signs of hyperdynamic state and heart failure under stress conditions, the diagnosis can be done with dosage of serum markers, electrocardiography, echocardiography and magnetic resonance. The treatment is mainly supportive, but orthotopic liver transplantation appears to improve this condition although the prognosis of liver transplantation in patients with cirrhotic cardiomyopathy is uncertain.